Performance Evaluation of Sustainable Concrete Pavements with Utilization of Reusable Waste Material (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The constant need for infrastructure development in the building industry brought about bypopulation growth led to increased use of aggregates and cement. Ultimately boosting carbon emissionsand resource extraction in greater depths. The focus here is to create sustainable concrete usingpartially replacing cement with supplementary cementitious material like Fly Ash (FA), Silica Fume (SF),and Recycled Coarse Aggregates (RCA) with virgin aggregate so that FA, SF, and RCA, can be usedwidely in construction.Concrete was produced for the study in various batches while maintaining a constant water-cement ratioof 0.4. Compressive strength and flexural strength tests are used to determine the hardened propertiesof the specimens after 3, 7, and 28 days of curing. Batches were altered based on the constituents thatwere substituted, adding 5, 10, and 15 for Fly Ash, 3, 6, and 9 for Silica Fume, and 0, 6,12, and 18 for Recycled Coarse Aggregates.The utilization of Fly Ash at 15, Silica Fume at 9, and Recycled Coarse Aggregates at 18demonstrated to have achieved significant outcomes after 28 days of testing. Numerous batches hadnotable results in the compressive test but struggled in the flexural test. Some batches including Fly Ashat 10, Silica Fume at 6, and Recycled Coarse Aggregates at 12 reached early age strength and didnot improve as age grew, whereas batches containing Fly Ash at 15, Silica Fume at 9, and RecycledCoarse Aggregates at 18 greatly improved over time.